2017
DOI: 10.1007/978-3-319-67687-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal vs. Vertical: How the Orientation of a Large Interactive Surface Impacts Collaboration in Multi-surface Environments

Abstract: Defining the form factor and setup of surfaces, i.e., their size, position, and orientation, is one of the first decisions made when designing multisurface environments (MSE). To support these choices, we conducted a study on how the orientation of a large display used alongside tablets impacts collaboration. Previous research involving only one interactive surface shows that display orientation changes how people interact with the display, the way they position themselves, or look at each other. Our study sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The rest of the participants discussed seated or standing, but refrained from interacting. This finding is supported by other studies on collaboration around interactive displays [47,53]. We note that although most participants did not interact directly with the display, they were however actively involved in the exploration.…”
Section: Scenarios and Trade-off Exploration [Q1]supporting
confidence: 89%
“…The rest of the participants discussed seated or standing, but refrained from interacting. This finding is supported by other studies on collaboration around interactive displays [47,53]. We note that although most participants did not interact directly with the display, they were however actively involved in the exploration.…”
Section: Scenarios and Trade-off Exploration [Q1]supporting
confidence: 89%
“…The authors found that a maptable-based solution can provide significant advantages when multiple users with different roles collaborate in sense making and planning tasks. Finally, the horizontal setup of a maptable revealed significant benefits for group collaboration compared to a vertical setup of the same device [29,30].…”
Section: Interactive Pss Toolsmentioning
confidence: 99%
“…as negative awareness indicators, and i) reaction without explicit request, ii) parallel work on same activity without verbal coordination, among others, as positive awareness indicators. Building on this work, Tong et al [22] compared horizontal vs. vertical surfaces with regards to collaboration and found out that in both conditions a good level of awareness could be maintained. However, in the vertical condition participants needed to do more explicit awareness work in the form of verbal shadowing.…”
Section: Related Workmentioning
confidence: 99%